Gambaran Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Rumah Sakit - Nurchamidin Gobel (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Patients are one indicator of the quality of services we provide and patient satisfaction is a capital to get more patients and to get loyal patients (faithful). Loyal patients will reuse the same health services if they need it again. Even loyal patients will invite others to use the same health service facility. The purpose of this study is to describe the level of patient satisfaction. This type of research uses a descriptive method with concurrent data collection. The data collected is in the form of result data (observations and questionnaires). Concurrent data is primary data obtained during direct observation and questionnaires during the research. This research was conducted from the second week of December 2020 until the end of February 2021. The data obtained is based on the answers from respondents to the questionnaire that has been tested for validity and reliability and then distributed. Furthermore, processed and analyzed and seen the percentage level of patient satisfaction which is presented in tabular form. Based on the data obtained from the respondents' answers, it can be concluded that the description of the level of patient satisfaction in the pharmacy installation of ZUS Hospital North Gorontalo is in the good category, with an average percentage of 81%. The criterion aspect of the question that received the most positive response from the respondents was that the service procedures at IFRSUD ZUS Gorontalo Utara were fast and did not bother the patient? (94%) and on the aspect of the criteria the question is that whether the officers are fair in providing services? (63%). Things that need to be done to improve aspects of questions that are still in the sufficient category are by improving the pharmaceutical service process as a whole, conducting supervision and awareness for all parties.